2018
DOI: 10.1123/ijsnem.2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Australian Football Athletes Lack Awareness of Current Sport Nutrition Guidelines

Abstract: Sports nutrition is an evolving field, but there is a lack of data on Australian athletes' knowledge of current sports nutrition guidelines. Additionally, several tools used to assess nutrition knowledge (NK) have not undergone adequate validation. The purpose of this study was to assess and compare the sports NK of elite and nonelite Australian football (AF) athletes using a newly validated questionnaire-The Nutrition for Sport Knowledge Questionnaire. Elite AF players (n = 46) were recruited directly from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 31 publications
5
50
4
Order By: Relevance
“…Lohman et al (2018) found that the majority of Australian footballers in their study over-consumed protein and under-consumed carbohydrate. The misunderstanding of nutrition advice revealed in our study is consistent with Lohman, Carr, and Condo (2018) and Trakman et al (2018) who found that Australian footballers' sports nutrition knowledge was "poor".…”
Section: Club Guidancesupporting
confidence: 88%
“…Lohman et al (2018) found that the majority of Australian footballers in their study over-consumed protein and under-consumed carbohydrate. The misunderstanding of nutrition advice revealed in our study is consistent with Lohman, Carr, and Condo (2018) and Trakman et al (2018) who found that Australian footballers' sports nutrition knowledge was "poor".…”
Section: Club Guidancesupporting
confidence: 88%
“…While overall NK was poor, participants performed best in macronutrient, weight management and sports nutrition sections (Table 3 ). A detailed description of professional and recreational AF players’ NK, assessed using the NSKQ are reported elsewhere [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that Australian athletes have low NK scores and fail to comply with best‐practice sports nutrition guidelines . As NK is one factor that can influence nutrition behaviour, it is pertinent to explore the preferred information sources that athletes use, and how preferences influence NK.…”
Section: Discussionmentioning
confidence: 99%
“…6 A sub-set of the NK data from study 1 is reported elsewhere. 8 For study 2, data were collected using the A-NSKQ; all the NK data from study 2 are reported elsewhere. 7 The questionnaires were self-administered online, making supervision impossible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation